Theory and Practical Procedure for Predicting S-N Curves at Various Stress Ratios - Kim, Ho Sung (Journal of Composites and Biodegradable Polymers, 2019)
Predictive models in the past for stress ratio effect on S-N fatigue life have been subject to modifications since the 19th century. Many of them have been developed with limited experimental verifications or beyond the theoretical limit. Also, they have employed weak S-N curve models for the development, resulting in inefficiency in applications. There has been, also, a missing link in the development of predictive models between S-N curve behaviour and stress ratio effect. In this paper, theoretical analysis is presented and subsequently a practical procedure for predicting S-N curves at various stress ratio is proposed. The theoretical and experimental characteristics of the constant fatigue life (CFL) diagram were clarified for capability and limitations, and dependence of experimental fatigue behaviour. Mathematical relationships between linear CFL lines and fatigue damage parameters were successfully derived. As a result, the Kim and Zhang S-N curve model was successfully dovetailed with the linear CFL lines to predict S-N curves for the whole range of stress ratios. Theoretical predictions of fatigue life based on the mathematical relationships were verified with experimental data.